Pengaruh corporate governance terhadap kinerja keuangan perusahaan manufaktur sektor food and beverage yang terdaftar di BEI tahun 2018-2020 - Nanda Safitri, Dea; Hariyati, Hariyati (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This research has purpose to evaluate the Influence of GC to Financial Performance of Food Sector And Baverage stock exchange in 2018-2020. There are two variables used, they are (1) Independent Variable, consist of : Independent Commissioner (X1), Board of Director (X2), Managerial Ownership (X3). (2) Dependence Variableis : Financial Performancewhich is wessured with Return On Assets (ROA) (Y). This study uses a quantitative method and data analysis technique is used : (1) Description of Statistic analysis, (2) Classical Assumption Test ( Auto Correlation, Normality, Heterocedarticity, and Multicolliniearity) and (3) Hypothesis Testing ( Test of T and Test of F). The result of researching shows that simultaneously of independence commissioner variable, board of director, and managerial ownership overally or simultaneously have influence tp financial performance which is registered in BEI period 2018-2020.